(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
Low financial literacy and digital technology adoption gap are the main challenges in improving the financial performance of MSMEs in Indonesia. This study aims to identify and analyze the relationship between financial literacy, digital transformation, and MSME performance through the Systematic Literature Review (SLR) approach. Data was collected from various open access scientific publications in 2020–2025. Analysis was carried out on relevant studies using the content analysis method. The results show that the integration between financial literacy and digital transformation is a strategic combination that has a significant impact on the performance and sustainability of MSMEs. This research makes a theoretical and practical contribution to the development of a digital-literacy-based MSME empowerment model.